Counting plants: The extent and adequacy of monitoring for a continental-scale list of threatened plant species. (August 2021) - Lavery, Tyrone; Lindenmayer, David; Blanchard, Wade; Carey, Alex; Cook, Emma; Copley, Peter; Macgregor, Nicholas A.; Melzer, Rhonda; Nano, Catherine; Prentice, Laura; Scheele, Ben C.; Sinclair, Steve; et al.
Abstract: Monitoring of threatened species is a critical part of conserving biodiversity. It is needed to understand population trajectories, threatening processes, and the type and effectiveness of management responses needed to ensure persistence and recovery. Characteristics of some plant species (e.g. immobility) should render them amenable to monitoring, whereas other characteristics (e.g. ephemeral life histories) will make plant monitoring challenging. We evaluated monitoring adequacy and extent for a large sample (839 taxa) of Australia's threatened plants (1336 taxa) and compared this assessment with a similar evaluation for threatened vertebrates. We found 37.2% of threatened plants are monitored, half the rate found for vertebrates. For monitored plants, monitoring quality as assessed using a set of nine criteria was generally low, similar to results for vertebrates. Plants with more imperilled conservation status were more likely to be monitored and tended to have higher quality monitoring. Plants with recovery plans were more likely to be monitored than those without. The likelihood a species was monitored decreased the longer a taxon had been listed under threatened species legislation. Monitoring longevity was poor but inclusion of demographic data and linkages to management were better than for vertebrates. Our assessment highlighted a lack of collated monitoring data for plants, and we recognise there are exemplary programs for threatened plants that can guide improvements in monitoring for other species. Plants are overwhelmingly represented in threatened species lists worldwide and a determined focus to improve the extent and quality of plant monitoring should underpin biodiversity conservation targets.